Inovasi Limbah Kayu Sungai Batang Serangan Untuk Meningkatkan Kesejaahteraan Masyarakat Desa Sei Serdang - Prayudi, Ahmad; Siregar, Nina Siti Salmaniah; Rambe, Yunita Safitri; Yusnini, Yusnini; Sari, Warsani Purnama; Rosalina, Dhian (Universitas Medan Area, 2024)
Sei Serdang Village, located in the Tangkahan Ecotourism area, is part of the Gunung Leuser National Park, a popular tourist destination. However, the Batang Serangan River, which runs through the village, poses a significant problem because its banks are filled with broken wood debris, creating a risk of flash floods. To address this, a program was initiated to train local souvenir and furniture craftsmen in Sei Serdang to manage the wood waste from the river. Through this waste management effort, production costs can be reduced, the river can be cleaned of wood debris, and the community's welfare can improve. The program employed a participatory approach, combining lectures, discussions, training, and monitoring. The stages included observation, wood waste design training, preservation, production, finishing, and final evaluation. Based on the evaluations, the craftsmen's understanding of wood waste management increased by 40%, business potential awareness by 10%, and river conservation awareness by 15%. Twenty out of forty participants successfully created innovative craft and furniture designs, while twenty-five participants utilized wood waste as production materials. Additionally, the use of wood waste led to production cost savings of up to 26.67% for souvenirs and 25% for more complex furniture items.